Plasma Exchange in Refractory Acute Disseminated Encephalomyelitis Associated with COVID-19: Technical Challenges in a Developing Country - Raut, Sumantra Kumar; Sarkar, Mihir; Khemka, Arpita; Datta, Kalpana; Nandi, Mousumi; Biswas, Durba; Sutar, Dipankar; Banerjee, Arundhati (Journal of Pediatric Neurology, 2021)
Evaluation of acquired demyelinating syndrome (ADS) without diagnostic biomarkers results in diagnostic and therapeutic challenges in pediatric population. Immune-mediated ADS of childhood responds well to steroid and intravenous immunoglobulin (IVIg) and in refractory cases with plasma exchange. Novel coronavirus disease 2019 (COVID-19) coinfection in such cases imposes technical challenges in management. An 11-year-old girl with quadriparesis and loss of vision and a magnetic resonance imaging (MRI) brain showing acute demyelinating encephalomyelitis (ADEM) and cerebrospinal fluid examination being noncontributory responded well with plasma exchange after failing steroid and IVIg is described. Coinfection with COVID-19 mandating personal protection in a temperate country imposed technical challenges in her management.
Keywords: COVID-19; ADEM; PLEX; NMO–MOG demyelination